2020
DOI: 10.1002/chem.201905608
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Rate Inside the Cavity of [Ga4L6]12− Supramolecular Metallocage is Regulated by the Encapsulated Solvent

Abstract: In the present study the dependenceo ft he reaction rate of carbon-carbon reductivee limination from R 3 PAu(MeOH)(CH 3 ) 2 (R = Me, Et) complexes inside [Ga 4 L 6 ] 12À metallocage on the nature of the phosphine ligand is investigated by computational means. The reductive elimination mechanism is analyzed in methanol solution and inside the metallocage. Classicalm olecular dynamics simulations reveal that the smallert he gold complex (which depends on the phosphine ligand size) the larger the number of solven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Computing reliable binding affinities can be a precious tool for designing supramolecular hosts. Based on previous studies on supramolecular systems, 14 , 15 , 18 , 32 , 33 , 65 , 72 several variables could relate to such prediction: (1) the cavity volume of the host alone, (2) the volume of the guest, (3) the packing values, that is, the ratio between the volume of the guest in front of the volume of the cavity of the host, and (4) the possible involvement of solvent molecules. It is likely although that the real relationship lies as a combination of these different factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computing reliable binding affinities can be a precious tool for designing supramolecular hosts. Based on previous studies on supramolecular systems, 14 , 15 , 18 , 32 , 33 , 65 , 72 several variables could relate to such prediction: (1) the cavity volume of the host alone, (2) the volume of the guest, (3) the packing values, that is, the ratio between the volume of the guest in front of the volume of the cavity of the host, and (4) the possible involvement of solvent molecules. It is likely although that the real relationship lies as a combination of these different factors.…”
Section: Resultsmentioning
confidence: 99%
“… 14 19 So far, the works performed were based on quantum chemistry approaches combined with limited conformational sampling performed via molecular dynamics (MD) (either based on force fields or quantum approaches). 14 , 15 , 17 − 20 These works were focused at decoding the particularities of the host–guest catalytic mechanism compared to the reaction taking place in solution. Among the most striking results was the identification that the few solvent molecules that access the host cavity are fundamental for the catalytic effect provided by the supramolecular assembly.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40][41][42][43][44][45][46][47] In the case of highly anionic hosts, as the [Ga 4 L 6 ] 12À metallocage, all computational studies show that electrostatic effects are crucial for the rate acceleration. [30][31][32][33]48,49] In our previous works, we studied the reductive eliminations from the Au(III) complexes, [R 3 PAu (MeOH)(CH 3 ) 2 ] + , in the [Ga 4 L 6 ] 12À and showed that not only encapsulation by the host, but also microsolvation plays an important role for lowering the Gibbs energy barrier of the reductive elimination from the Au(III) complexes inside [Ga 4 L 6 ] 12À . [30,31] In the present study, we investigate computationally the origin of the catalysis observed for alkyl-alkyl reductive elimination from the Pt(IV)-complex, [trans-(Me 3 P) 2 Pt-(MeOH)(CH 3 ) 3 ] + , 2P.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33]48,49] In our previous works, we studied the reductive eliminations from the Au(III) complexes, [R 3 PAu (MeOH)(CH 3 ) 2 ] + , in the [Ga 4 L 6 ] 12À and showed that not only encapsulation by the host, but also microsolvation plays an important role for lowering the Gibbs energy barrier of the reductive elimination from the Au(III) complexes inside [Ga 4 L 6 ] 12À . [30,31] In the present study, we investigate computationally the origin of the catalysis observed for alkyl-alkyl reductive elimination from the Pt(IV)-complex, [trans-(Me 3 P) 2 Pt-(MeOH)(CH 3 ) 3 ] + , 2P. The analysis is performed first in solution and then inside the metallocage, [Ga 4 L 6 ] 12À , 3, (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation